Influencia de la lecto-escritura en el desarrollo de la fluidez verbal de los estudiantes del 7mo año de educación general básica de la Unidad Educativa Darío C. Guevara, de la ciudad de Babahoyo, parroquia El Salto, Provincia de Los Ríos - Becilla Moreno, Leonela Elizabeth (2019)
Through the present Final Report of the Research Project will be carried out in the Educational Unit "Darío C. Guevara", from the city of Babahoyo, Parroquia El Salto, Province of Los Ríos, whose theme is: Influence of reading and writing in the development of the verbal fluency of the students of the 7th year of General Basic Education of the Educational Unit "Darío C. Guevara", of the city of Babahoyo, Parroquia El Salto, Province of Los Ríos, in order to determine in what way The strategies and techniques of reading and writing influence the verbal fluency of students in the 7th year of General Basic Education. Nowadays, the social context, the Ecuadorian education looks for to form integral to the student (a), with a view to that this one manages to develop his capacities, values and attitudes. This requires specialized and / or updated training that allows teachers to promote verbal fluency in students so that they can face the different challenges posed by society. The present final report of the research project is considered very feasible because of the opportunity to know about the factors that determine verbal fluency in students in the area of language and literature through literacy skills.